Dorota Muszytowska, Etos chrześcijańskiej wspólnoty. Socjoretoryka Listu Jakuba (Warszawa: Wydawnictwo UKSW 2016) - Pikor, Wojciech (The Biblical Annals, 2017)
Book review: Dorota Muszytowska, Etos chrześcijańskiej wspólnoty. Socjoretoryka Listu Jakuba (Warszawa: Wydawnictwo UKSW 2016). Ss. 357. PLN 27.00. ISBN 978838900981.